Finding Jingga and Other Stories: Creating Children’s Picture Books Exploring Disenfranchised Grief - Helen Hodiono; Stefanny Irawan (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This paper revolves around disenfranchised grief in children. Disenfranchised grief refers to a loss that is not acknowledged, not socially accepted, and not discussed in public which makes people think that they have no right to grieve that loss. With children’s picture books as the chosen creative form and adventure as the chosen genre, this paper presents what causes children to grieve and how they process this grief. The stories depict Putra, Gwen, Daniel, Deborah, and Gabriel experiencing disenfranchised grief because their attachment to people or things they care about is broken, regardless of how trivial it is. Onward, they process grief by going through John Bowlby and Colin Murray Parkes’s four phases of grieving namely numbness, yearning and searching, disorganization, and re-organization to seize acceptance.